2021
DOI: 10.1186/s40677-021-00187-x
|View full text |Cite
|
Sign up to set email alerts
|

A comparative geological, tectonic and geomorphological assessment of the Charlotte, Regent and Madina landslides, Western area, Sierra Leone

Abstract: This work focused on three landslide events that have attracted significant public concern due to the associated calamities they recorded in 1945, 2017 and 2019, i.e. the Charlotte, Regent and Madina landslides, respectively. Their geology, tectonics (structural discontinuities) and geomorphology, i.e. their GTG characteristics were studied to establish links between them and the landslide events.Field surveys were conducted, particularly on the Charlotte landslide, where the identification of geological struc… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
2
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 60 publications
1
2
0
1
Order By: Relevance
“…The European screening is quite consistent with what was detected in the case of the landslide inventory implemented by Solís-Castillo et al [62] as regards the Mexican tropical region of Sierra Costa, characterized by low precipitation rates and landslide hazard diffused over mountainous and plain zones. Analogous findings are shown, among many, in recent studies concerning the Freetown region in Sierra Leone [63], and the Whitsunday Region, located in North Queensland, Australia [64].…”
Section: Discussionsupporting
confidence: 86%
“…The European screening is quite consistent with what was detected in the case of the landslide inventory implemented by Solís-Castillo et al [62] as regards the Mexican tropical region of Sierra Costa, characterized by low precipitation rates and landslide hazard diffused over mountainous and plain zones. Analogous findings are shown, among many, in recent studies concerning the Freetown region in Sierra Leone [63], and the Whitsunday Region, located in North Queensland, Australia [64].…”
Section: Discussionsupporting
confidence: 86%
“…Additional geotechnical drilling and investigation are required to provide deep-seated structural information, knowledge of secondary minerals present in joints, and characterisation of soil material in the hills (Lahai et al 2021 ).…”
Section: Resultsmentioning
confidence: 99%
“…These measures facilitated the triggering of the landslides by a sudden storm of intense rainfall (cf. Lahai et al 2021). However, a closer check using ground reality and satellite photographs revealed that the Kokkayar landslide was completely caused by humans, whereas the Plappally landslide was also affected by geomorphic and tectonic causes.…”
Section: Discussionmentioning
confidence: 99%